Market Orientation and Business Performance: Evidence from Libya - G. M. Elkrghli, Dr. Sabri (Scientific Journal of University of Benghazi, 2026)
Purpose - This paper focuses on exploring the extent to which organisations in Libya adopt the concept of market orientation under economic reforms. The study examines the influences of type of business; ownership type, on market orientation adoption and hence, business performance. Methodology - Questionnaire survey was used to collect data. 400 questionnaires were circulated only 276 returned with 233 considered valid for data analysis stage. Narver and Slater‟s construct (1990) was adopted to measure market orientation and business performance measured subjectively by high level executives‟ perception to their businesses‟ performances against their counterparts in the Libyan market. Findings - The results revealed that there is growing level of market orientation embracing in Libya especially in the private sector, which is judged to be best performance. The study exposed positive association between market orientation and business performance, thereby underpinning previous findings internationally documented in the US, UK, Europe and transitional economies literature. Implications – Originality / Value - The value of the paper is that it comes as a response to scholars who have called for investigating market orientation practices in different cultural contexts. Hence, it fills the gap in the literature. Also, foreign businesses who have the desire to do business in Libya might consult such research. Finally, the study ends up with research implications; limitations and future research.